Glycosylated zein-chondroitin sulfate composite nanoparticles loaded with betulinic acid as well as preparation method and application of glycosylated zein-chondroitin sulfate composite nanoparticles
By combining glycosylated zein with chondroitin sulfate, anti-solvent method was used to prepare composite nanoparticles loaded with beta-based acid, which solved the problems of beta-based acid stability and bioavailability, and achieved high encapsulation rate and significant antitumor activity.
Patent Information
- Application Number
- CN202411291592.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art has failed to effectively improve the stability and bioavailability of beta acid, and its anti-tumor activity has not been fully exerted.
By glycosylation of zein and binding with chondroitin sulfate, composite nanoparticles loaded with beta-acid were prepared by anti-solvent method, and the process was optimized to improve the encapsulation rate and bioavailability.
The prepared composite nanoparticles have stable structure, uniform particle size, encapsulation rate as high as 96.89%, excellent sustained release characteristics and water dispersion, which significantly improves the anti-tumor activity of betasteic acid.
Smart Images

Figure CN119157856A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of pharmaceutical technology, and relates to composite nanoparticles loaded with betulinic acid, and specifically to glycosylated zein-chondroitin sulfate composite nanoparticles loaded with betulinic acid, and a preparation method and application thereof. Background Art
[0002] The main ways in which polysaccharides interact with proteins are covalent grafting and electrostatic interaction. Protein glycosylation is the covalent bonding between proteins and reducing sugars, based on the Maillard reaction mechanism. The Maillard reaction process is mainly divided into three stages: the initial stage, the intermediate stage, and the advanced stage. The initial stage includes the condensation of the free ε-amino groups of protein molecules (mainly lysine and serine) with the reducing ends of the carbonyl groups of polysaccharide molecules to produce the Amadori rearrangement reaction, forming a Schiff base to obtain the Amadori product. The intermediate stage includes the degradation of the Amadori product to produce furfural and ketone compounds. The advanced stage mainly produces nitrogen-containing polymers (melanoids). The main factors affecting the Maillard reaction between proteins and polysaccharides include the ratio of protein to polysaccharide, reaction temperature and time, relative moisture, the structure and molecular weight of the polysaccharide, etc. The covalent grafts and electrostatic complexes formed by polysaccharides and proteins can change the structure and functional properties of proteins, especially they can adjust the hydrophobicity and hydrophilicity of proteins, and can be used to encapsulate bioactive substances. Polysaccharides are also resistant to digestion, so the release of encapsulated bioactive substances can be controlled.
[0003] Zein is a food protein widely found in plants and has unique film-forming properties. Zein self-assembles in an ethanol-water solution as the solvent evaporates to form nanoparticles. The protein / polysaccharide soluble complex has strong foaming and emulsifying properties and can be used as a carrier material for embedding and protecting bioactive ingredients.
[0004] Betulinic acid (BA) is an active ingredient with anti-tumor effects, and has a significant inhibitory effect on various tumor cells such as lung cancer, ovarian cancer, cervical cancer, breast cancer, and melanoma.
[0005] Chondroitin sulfate (CS) is a sulfated mucopolysaccharide composed of N-acetylgalactosamine and glucuronic acid, which can be used for nano-delivery of hydrophobic and unstable active substances.
[0006] The prior art (Zhang Jinbo. Study on the modification of soybean protein by polysaccharide and its interface, emulsification and gel properties [D]. South China University of Technology, 2014) discloses the emulsification properties of soybean protein isolate-maltodextrin saccharification products prepared by high temperature and short time dry heat method. Soy protein was amphiphilically modified by Maillard reaction and restricted enzymatic hydrolysis to obtain a graft copolymer with an amphiphilic structure. The interface, emulsification and gel properties of soybean protein were improved by the modification of protein by polysaccharide. Soy protein / beet pectin soluble complex was prepared by using the electrostatic interaction between protein and polysaccharide, and the mechanism of the complex stabilizing water-in-oil emulsion was analyzed.
[0007] The prior art (Ren Xiaoming. Preparation of Zein and Zein Peptide Composite Nanoparticles and Study on Their Transport and Antioxidant Properties [D]. South China University of Technology, 2015) discloses that the co-assembly technology induced by supercritical CO2 anti-solvent technology was used to prepare soy isoflavone / zein composite nanoparticles with small particle size, high loading rate and good colloidal stability, taking Zein and Zein peptide as the research objects. The composite nanoparticles of Zein peptide and α-tocopherol (TOC) were prepared by the water-based anti-solvent method, and the colloidal particle stability, transport performance and antioxidant activity of the composite nanoparticles formed by the Zein peptide (non-aqueous phase Zein peptide) prepared under non-aqueous phase conditions and the Zein peptide (aqueous phase Zein peptide) prepared under aqueous phase conditions were systematically compared. In order to improve the pH stability of TOC / Zen peptide composite nanoparticles, the glycosylation product of Zein peptide-maltodextrin was prepared by Maillard reaction, and then the composite nanoparticles of TOC / Zen peptide-maltodextrin glycosylation product were prepared by the water-based anti-solvent method. Dynamic light scattering and atomic force microscopy analysis showed that the glycosylation product and TOC can be co-assembled to form spherical nanoparticles. Compared with corn peptide and corn peptide / maltodextrin mixture, TOC / corn peptide-maltodextrin glycosylation product composite nanoparticles do not aggregate under low pH conditions, and the solution remains transparent. Corn peptide-maltodextrin glycosylation product also has better protection and sustained-release effects on TOC.
[0008] The invention patent with publication number CN107595809A discloses a zein nano-embedded sustained-release filler and a preparation method thereof, wherein the zein nano-embedded sustained-release filler comprises the following raw materials in parts by weight: 5-15 parts of zein and 2-10 parts of an anti-tumor drug. The anti-tumor drug is one or any combination of cisplatin, doxorubicin, paclitaxel, 5-fluorouracil, etoposide, and vincristine.
[0009] The invention patent with publication number CN113730373B discloses a zein AOS composite nanoparticle for delivering curcumin and a preparation method thereof. The zein-AOS composite nanoparticles are composed of corn alcohol-soluble protein (zein) and brown algae oligosaccharide (AOS). Curcumin is loaded into the zein-AOS composite nanoparticles to form Cur / zein-AOS composite nanoparticles. The encapsulation rate of curcumin reaches 89.7%, and it has the performance of gastrointestinal sustained release. Curcumin is fully released in the intestinal fluid, and the release rate reaches 83.8%.
[0010] None of the above technologies discloses glycosylated zein-chondroitin sulfate composite nanoparticles loaded with betulinic acid. In order to further improve the stability and bioavailability of betulinic acid and enhance its anti-tumor activity, improvements are still needed. Summary of the invention
[0011] The present invention aims at the problems existing in the prior art and provides a glycosylated zein-chondroitin sulfate composite nanoparticle loaded with betulinic acid and a preparation method and application thereof. The present invention glycosylates protein, selects anionic polysaccharide CS as a protein particle interface stabilizer, prepares glycosylated zein-CS composite nanoparticles by an antisolvent method, and uses the glycosylated zein-CS composite nanoparticles to load betulinic acid. Through process optimization, nanoparticles with high encapsulation rate are prepared, which can improve the bioavailability and anti-tumor activity of betulinic acid.
[0012] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0013] In a first aspect, the present invention provides a method for preparing glycosylated zein-chondroitin sulfate composite nanoparticles loaded with betulinic acid, which are prepared from betulinic acid, glycosylated zein and chondroitin sulfate by an anti-solvent method.
[0014] The glycosylated zein is obtained by subjecting zein to a glycosylation reaction using glucose, and the glycosylation reaction specifically comprises the following steps:
[0015] The zein solution is dissolved in a KCl-NaOH buffer solution with a concentration of 0.1-0.3 mol / L and a pH value of 12.0-14.0, and glucose is added to the zein solution to cause a Maillard reaction, and the reaction is carried out at 80-90° C. for 1-4 hours, and the supernatant is separated by centrifugation, and the pH value of the supernatant is adjusted to 7.0 with hydrochloric acid; the obtained supernatant solution is dialyzed and then dried to obtain glycosylated zein. The grafting degree of the glycosylated zein is 20-25%.
[0016] In one embodiment, the glycosylation reaction specifically includes the following steps: dissolving zein powder in a KCl-NaOH buffer solution with a concentration of 0.2 mol / L and a pH value of 13.0, magnetically stirring until the zein is completely dissolved to obtain a zein solution, and then adding glucose to the zein solution under magnetic stirring and constant temperature heating to allow the zein to undergo a Maillard reaction with the sugar, reacting at 85°C for 2 hours, immediately placing the mixed solution in ice water to stop the reaction, centrifuging the supernatant, and adjusting the pH value of the supernatant to 7.0 with hydrochloric acid; dialyzing the obtained supernatant solution, and then drying, and the obtained powder is a glycosylated zein (named G-zein) powder. The grafting degree of the glycosylated zein is 22.8%.
[0017] In one embodiment, in the glycosylation reaction, the mass ratio of zein to glucose is 1-5:1, preferably 2-5:1, and can be 2:1, 3:1, 4:1, 5:1, and more preferably 2:1.
[0018] In one embodiment, in the glycosylation reaction, the concentration of the zein solution is 5-50 mg / mL, preferably 10-20 mg / mL, and more preferably 10 mg / mL.
[0019] The mass ratio of betulinic acid, glycosylated zein and chondroitin sulfate is 1-9:1-5:1-5, preferably 2-5:4-5:1-5. More preferably, the mass ratio of betulinic acid, glycosylated zein and chondroitin sulfate is 2-5:4:1. In one embodiment, the mass ratio of glycosylated zein and chondroitin sulfate is 1-5:1-5, preferably 1-5:1, more preferably 4-5:1. In one embodiment, the mass ratio of glycosylated zein and chondroitin sulfate is 4:1.
[0020] The anti-solvent method is a process of forming droplets by dispersing a liquid in another immiscible liquid, also known as a liquid-liquid dispersion method. Glycosylated zein is dissolved in an ethanol solution, and then dispersed in an aqueous phase system at a certain homogenization rate to reduce the solubility of glycosylated zein, and the molecules aggregate under the action of the self-assembly property, thereby gradually forming nanoparticles.
[0021] The anti-solvent method is specifically:
[0022] Step 1): dissolving betulinic acid in an ethanol aqueous solution of glycosylated zein, wherein the volume fraction of the ethanol aqueous solution is 65-74%, preferably 70%, to obtain solution 1; Step 2): mixing an aqueous solution of chondroitin sulfate with the solution 1 for reaction to obtain glycosylated zein-chondroitin sulfate composite nanoparticles loaded with betulinic acid.
[0023] In one embodiment, the anti-solvent method is specifically as follows: betulinic acid is dissolved in an ethanol aqueous solution of glycosylated zein, the volume fraction of the ethanol aqueous solution is 70%, to obtain solution 1, the concentration of betulinic acid in the solution 1 is 2.5-4.5 mg / mL; an aqueous solution of chondroitin sulfate is mixed with the solution 1 at a volume ratio of 40-60:1 for reaction, the concentration of the aqueous solution of chondroitin sulfate is 0.01-0.1 mg / mL, the reaction time is 0.5-2h, preferably 1h, to obtain glycosylated zein-chondroitin sulfate composite nanoparticles loaded with betulinic acid.
[0024] In a second aspect, the present invention provides betulinic acid-loaded glycosylated zein-chondroitin sulfate composite nanoparticles prepared by the preparation method, wherein the particle size of the composite nanoparticles is 160-180 nm.
[0025] In a third aspect, the present invention provides the use of the composite nanoparticles or the composite nanoparticles prepared by the preparation method in the preparation of anti-tumor drugs. Preferably, the tumor includes liver cancer.
[0026] Compared with the prior art, the present invention has the following beneficial effects: the present invention performs a glycosylation reaction on zein to obtain glycosylated zein, and the glycosylated zein and chondroitin sulfate are compounded by protein-polysaccharide to embed betulic acid in an amorphous state inside the particles formed by protein-polysaccharide. Compared with the composite nanoparticles prepared by unglycosylated zein, the glycosylated zein-chondroitin sulfate composite nanoparticles loaded with betulic acid prepared by the present invention have a stable structure, uniform distribution, a particle size of 160-180nm, an encapsulation rate of 96.89%, excellent sustained release characteristics and water dispersibility, better bioavailability, and can improve the anti-tumor activity of betulic acid. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Schematic diagram of preparing protein-polysaccharide composite nanoparticles loaded with BA;
[0028] Figure 2The figure shows the effect of BA concentration on the particle size and encapsulation efficiency of G-zein@BA-CS and zein@BA-CS, where A shows the effect of BA concentration on particle size (AD, p < 0.05; ae, p < 0.05), and B shows the effect of BA concentration on encapsulation efficiency;
[0029] Figure 3 is the XRD spectrum of the sample;
[0030] Figure 4 TEM images of nanoparticles, where A is the microscopic image of zein-CS, B is the microscopic image of G-zein-CS, C is the microscopic image of zein@BA-CS, and D is the microscopic image of G-zein@BA-CS;
[0031] Figure 5 In vitro release graph and water dispersibility graph of the particles, wherein A is the in vitro release graph of the particles in PBS with a pH of 7.4, and B is the water dispersibility graph of the particles (p < 0.05);
[0032] Figure 6 The cell activity diagrams of HepG2 cells after the nanoparticles acted on them for 24h and 48h, where A is the 24h diagram and B is the 48h diagram;
[0033] Figure 7 The results of HepG2 cells phagocytizing coumarin-6 labeled G-zein@BA-CS nanoparticles, A is the CLSM image, B is the flow cytometry study result, and C is the quantitative result of cell phagocytosis (p < 0.05);
[0034] Figure 8 The results of HepG2 cells phagocytizing coumarin-6 labeled zein@BA-CS nanoparticles, A is the CLSM image, B is the flow cytometry study result, and C is the quantitative result of cell phagocytosis (p < 0.05);
[0035] Fig. 9 Immunofluorescence images of microtubules in HepG2 cells after treatment with free BA, zein@BA-CS and G-zein@BA-CS for 24 hours;
[0036] Fig.10 Figure 1 is the effect of nanoparticles on cell apoptosis, where A is the effect of nanoparticles on cell apoptosis after HepG2 cells were treated with nanoparticles detected by flow cytometry (cell scatter plot), and B is the percentage of cell apoptosis caused by nanoparticles (the sum of the percentage of early and late apoptosis) (p < 0.05);
[0037] Fig.11This is the effect of nanoparticles on genes in the Caspase-3 signaling pathway of cell apoptosis (p < 0.05);
[0038] Fig.12 The figure is the effect of nanoparticles on the protein of Caspase-3 signaling pathway of cell apoptosis, wherein A is the expression of apoptosis-related protein, and B is the statistical analysis result of the expression of apoptosis-related protein (p<0.05). DETAILED DESCRIPTION
[0039] It is worth noting that, unless otherwise specified, the raw materials used in the present invention are all common commercially available products, and their sources are not specifically limited.
[0040] Materials: Betulinic acid (BA) with a purity of ≥98% was purchased from Nanjing Chunqiu Bioengineering Co., Ltd.; zein (92% protein content), dimethyl sulfoxide (DMSO), and paraformaldehyde were purchased from Sigma-Aldrich, USA; chondroitin sulfate (CS) was purchased from Shandong Yibao Biological Products Co., Ltd.; potassium bromide (spectral grade) was purchased from Sinopharm Group; coumarin-6 was purchased from Shanghai Myrel Chemical Technology Co., Ltd.; human hepatoma cell HepG2 was purchased from the Chinese Academy of Sciences; fetal bovine serum (FBS), DMEM high-glucose culture, and trypsin digestion solution were purchased from Gibco, USA; penicillin and streptomycin were purchased from Harbin Pharmaceutical Group; Triton X-100, bovine serum albumin, CCK-8 kit, and Annexin V-FITC apoptosis detection kit were purchased from Beijing Solebao Company; 5× protein loading buffer, DAPI, and LysoTracker Red were purchased from Xi'an Het Biotechnology Co., Ltd.
[0041] Instruments: nano-laser particle size analyzer (ZEN3600, Malvern, UK), constant temperature magnetic stirrer (S22-2, Shanghai Siler Instrument Co., Ltd.), transmission electron microscope (JEM-1230, Japan Electronics Co., Ltd.), pH meter (PB-10, Sartorius, Germany), rotary evaporator (R-100, Buchi, Switzerland), high-speed centrifuge (GL-10MD, Hunan Xiangyi Co., Ltd.), freeze dryer (FD5-series, Jinximeng Instrument Co., Ltd., Ximeng International Group), water bath constant temperature oscillator (SHA-BA, Honghua Instrument Factory, Jintan, Jiangsu), carbon dioxide incubator and Fluoroskan multifunctional microplate reader (ThermoScientific, USA), high performance liquid chromatograph (Agilent, USA), X-ray diffractometer (Bruker, Germany), inverted fluorescence microscope (DMI4000B, Leica, Germany), flow cytometer (Tecan, Switzerland), laser confocal scanner (CLSM, Carl Zeiss, Germany).
[0042] Data analysis method: SPSS19.0 was used to analyze the data, and the results were expressed as mean ± standard deviation. One-way analysis of variance was used to test the significance of the test results, and Turkey method was used for multiple comparisons, where P < 0.05 indicated a significant difference.
[0043] Basic Example 1
[0044] Preparation of Glycosylated Zein (G-zein)
[0045] The preparation method comprises the following steps: dissolving 1 g of corn alcohol-soluble protein (zein) powder in 100 mL of KCl-NaOH buffer solution with a concentration of 0.2 mol / L and a pH value of 13.0, stirring the solution magnetically until the zein is completely dissolved to obtain a zein solution, and then adding 0.5 g of glucose to the zein solution under the action of magnetic stirring and constant temperature heating to allow the zein to undergo a Maillard reaction with the sugar. After reacting at 85° C. for 2 hours, the mixed solution is immediately placed in ice water for cooling to stop the reaction, separating the supernatant by centrifugation, and adjusting the pH value of the supernatant to 7.0 with hydrochloric acid; dialyzing the obtained supernatant solution, and then drying the obtained powder, namely, glycosylated corn alcohol-soluble protein (named as G-zein) powder, wherein the grafting degree of the G-zein is 22.8%.
[0046] Basic Example 2
[0047] Preparation of Glycosylated Zein-Chondroitin Sulfate Composite Nanoparticle Suspension
[0048] 0.5 g of G-zein (prepared in basic example 1) powder was added to 100 mL of 70% (v / v) ethanol solution, and magnetic stirring was performed until the protein was completely dissolved to obtain a G-zein solution. 5.00 mg, 2.50 mg, 1.67 mg, 1.25 mg and 1.00 mg of CS powder were weighed respectively, and completely dissolved in 50 mL of distilled water to obtain CS solutions of different concentrations. 1 mL of G-zein solution was added dropwise to 49 mL of CS solutions of different concentrations with a syringe and stirred for 60 min, so that the mass ratio of G-zein to CS was 1:1, 2:1, 3:1, 4:1, 5:1, and the protein-polysaccharide composite nanoparticle suspension formed was a glycosylated zein-chondroitin sulfate composite nanoparticle (named G-zein-CS nanoparticle) suspension.
[0049] Basic Example 3
[0050] Preparation of zein-chondroitin sulfate composite nanoparticle suspension
[0051] A zein-chondroitin sulfate composite nanoparticle suspension was prepared according to the method of Basic Example 2. The difference from Basic Example 2 was that the G-zein powder was replaced with zein (zein) powder to obtain a zein-chondroitin sulfate composite nanoparticle (zein-CS nanoparticle) suspension.
[0052] Example 1-2
[0053] according to Figure 1 The steps of preparing BA-loaded G-zein-chondroitin sulfate composite nanoparticle suspension (Example 1) and BA-loaded zein-chondroitin sulfate composite nanoparticle suspension (Example 2). Figure 1 Schematic diagram of the preparation of BA-loaded composite nanoparticles.
[0054] Specifically, the preparation method of the G-zein-chondroitin sulfate composite nanoparticle suspension loaded with BA is as follows: 0.5 g of G-zein powder is added to 100 mL of 70% (v / v) ethanol solution, magnetic stirring is performed until the protein is completely dissolved to obtain a G-zein solution, BA powder is added to the G-zein solution by a liquid-liquid dispersion method, so that the final concentration of BA is 2.5, 3, 3.5, 4, and 4.5 mg / mL, respectively, stirring and ultrasonic dissolution are performed at room temperature until BA is completely dissolved to obtain a G-zein nanoparticle solution loaded with BA. 1 mL of the G-zein nanoparticle solution loaded with BA is respectively added dropwise to 49 mL of CS solution of different concentrations with a syringe and stirred for 60 minutes, so that the mass ratio of G-zein to CS is 1:1, 2:1, 3:1, 4:1, and 5:1, to obtain a composite nanoparticle suspension loaded with BA, that is, a G-zein-chondroitin sulfate composite nanoparticle (G-zein@BA-CS nanoparticle) suspension loaded with BA.
[0055] Specifically, the preparation method of the zein-chondroitin sulfate composite nanoparticle suspension loaded with BA is as follows: 0.5 g of zein powder is added to 100 mL of 70% (v / v) ethanol solution, magnetic stirring is performed until the protein is completely dissolved to obtain a zein solution, BA powder is added to the zein solution by a liquid-liquid dispersion method, so that the final concentration of BA is 2.5, 3, 3.5, 4, and 4.55 mg / mL, respectively, stirring and ultrasonic dissolution are performed at room temperature until BA is completely dissolved to obtain zein nanoparticle solutions loaded with BA of different concentrations. 1 mL of the zein nanoparticle solution loaded with BA is respectively added dropwise to 49 mL of CS solutions of different concentrations with a syringe and stirred for 60 minutes, so that the mass ratio of zein to CS is 1:1, 2:1, 3:1, 4:1, and 5:1, to obtain a composite nanoparticle suspension loaded with BA, that is, a zein-chondroitin sulfate composite nanoparticle (zein@BA-CS nanoparticle) suspension loaded with BA.
[0056] Example 3
[0057] 1. Determination of particle size, PDI (polymer dispersibility index) and zeta potential of the composite nanoparticles obtained in Basic Examples 2-3 and Example 1-2, and determination of encapsulation efficiency of the composite nanoparticles obtained in Example 1-2.
[0058] Determination method:
[0059] (1) Determination of the encapsulation efficiency of the composite nanoparticles obtained in Example 1-2: The encapsulation efficiency of BA was determined by ultrafiltration centrifugation. Specifically, 1 mL of freshly prepared zein-chondroitin sulfate composite nanoparticle suspension loaded with BA was added dropwise to an ultrafiltration tube with a molecular weight cutoff of 10 KDa, centrifuged at 4000 rpm for 30 min, the filtrate overflowing the filter membrane was taken out, and 1 mL of methanol was added to the ultrafiltration tube for further centrifugal extraction. The above operation was repeated twice to combine the filtrate, and after filtering through a 0.22 μM organic filter membrane, HPLC was used for detection. The detection conditions were: the chromatographic column was a Waters Symmetry C18 column (5 μm, 250 mm×4.6 mm), the mobile phase was composed of acetonitrile: water (75:25%, v / v), the flow rate was 1.0 mL / min, the detection wavelength was 210 nm, and the column temperature was maintained at 30°C. The encapsulation efficiency calculation formula of BA is as follows:
[0060]
[0061] (2) Determination of the particle size, PDI (polymer dispersibility index) and zeta-potential of the zein-chondroitin sulfate composite nanoparticles and BA-loaded zein-chondroitin sulfate composite nanoparticles obtained in Basic Examples 2-3 and Example 1-2: Use a nano-laser particle size analyzer to determine the particle size of the nanoparticles. Dilute the nanoparticle suspension sample to be tested to 100 times and then determine the average particle size and PDI value of the sample. PDI represents the particle size distribution. Generally speaking, the lower the PDI, the more uniform the particle distribution and the more stable the sample. All measurements were carried out at 25°C. At least 10 sets of data were collected for each sample, and the measurement was repeated 3 times to obtain the average value. The zeta-potential was determined using the Smoluchowski mode. The test temperature was 25°C, and each sample was measured three times.
[0062] Test results
[0063] Both polysaccharide and protein molecules carry electric charge. When polysaccharide and protein are compounded, the size and property of the electric charge are closely related to the mass they occupy, and the electrostatic interaction between the two also changes accordingly. The change of the compound ratio of polysaccharide and protein also affects the particle size and PDI (polymer dispersibility index) of the composite nanoparticles. The particle size, PDI and zeta potential of the composite nanoparticles obtained in basic examples 2-3 are shown in Table 1.
[0064] Table 1 Properties of the composite nanoparticles obtained in Basic Examples 2-3
[0065]
[0066] The results in Table 1 show that when the mass ratio of zein / G-zein and CS is 4:1, the particle sizes of zein-CS and G-zein-CS nanoparticles reach the minimum, which are 164.1nm and 144.9nm respectively, and the PDI is less than 0.11. At this time, the protein and polysaccharide are most tightly complexed, and the particle size of G-zein-CS nanoparticles is smaller than that of zein-CS nanoparticles, indicating that compared with zein-CS nanoparticles, G-zein and CS are more tightly bound.
[0067] Zein has a large number of hydrophobic region structures, and BA is a hydrophobic compound. When BA and zein are combined, there is a hydrophobic interaction between the two. This interaction can be maintained for a certain period of time so that BA is effectively loaded in the carrier. When the BA concentration is 50μg / mL, the properties of the composite nanoparticles loaded with BA are shown in Table 2.
[0068] Table 2 Effect of the properties of nanoparticles obtained in Example 1-2
[0069]
[0070] As shown in Table 2, under the same BA loading condition, as the mass ratio of zein to CS increases from 1:1 to 4:1, the particle size of zein-CS composite nanoparticles loaded with BA gradually decreases from 306.3nm to 189.9nm, and the encapsulation efficiency increases from 70.43% to 94.05%; the particle size of G-zein-CS composite nanoparticles loaded with BA gradually decreases from 290.3nm to 164.9nm, and the encapsulation efficiency increases from 77.51% to 96.89%. Further increasing the mass ratio of protein to polysaccharide to 5:1, the particle size of composite nanoparticles loaded with BA shows an increasing trend, which is higher than the particle size of blank nanoparticles (180.6nm) at the same mass ratio. When the mass ratio of zein / G-zein to CS is 4:1, the composite nanoparticles loaded with BA have smaller particle size and higher encapsulation efficiency, and G-zein@BA-CS has smaller particle size and higher encapsulation efficiency than zein@BA-CS. The composite structure formed by G-zein and CS is more stable and compact.
[0071] 2. Effect of BA loading on drug-loaded nanoparticles
[0072] The mass ratio of zein / G-zein to CS was fixed at 4:1, and the BA concentrations were 50 μg / mL, 60 μg / mL, 70 μg / mL, 80 μg / mL, 90 μg / mL, and 100 μg / mL, respectively, to explore the effect of different BA loading amounts on drug-loaded nanoparticles. Figure 2 As shown, Figure 2Figure 3 is the effect of BA concentration on the particle size and encapsulation efficiency of G-zein@BA-CS and zein@BA-CS, where A is the effect of BA concentration on particle size (AD, p < 0.05; ae, p < 0.05), and B is the effect of BA concentration on encapsulation efficiency.
[0073] Figure 2 The results show that with the increase of BA concentration (50-80μg / mL), the particle size of zein@BA-CS and G-zein@BA-CS showed an overall decreasing trend. When the BA concentration was 80μg / mL, the particle size of the obtained nanoparticles was the smallest, and the particle sizes of zein@BA-CS and G-zein@BA-CS reached 190.5nm and 182.5nm, respectively, and the encapsulation efficiency reached the maximum (95.67% and 96.41%), respectively. The composite structure formed by zein / G-zein and CS is more stable and compact, and has a stronger interaction with BA. When the BA concentration increased to 90-100μg / mL, the particle size of the obtained nanoparticles became larger and the encapsulation efficiency decreased. This may be because the hydrophobic interaction between the hydrophobic compound and the protein is closely related to the concentration of the two. When the concentration of the hydrophobic compound is low, the hydrophobic interaction maintains the stability of the nanoparticles and the two are tightly bound. When the concentration of the hydrophobic compound reaches a certain value, the hydrophobic interaction cannot maintain the steady state of the nanoparticles, resulting in its imbalance. The compound escapes from the nanoparticles and attaches to the surface, and the particle size of the nanoparticles increases. Comparing zein@BA-CS and G-zein@BA-CS prepared at the same BA concentration, it is found that G-zein@BA-CS has a smaller particle size and a higher encapsulation rate. The composite structure formed by G-zein and CS is more stable and tight, and has a stronger interaction with BA.
[0074] Example 4
[0075] Samples: zein; BA; G-zein obtained in basic example 1; zein-CS and G-zein-CS nanoparticles obtained in basic examples 2 and 3 with a zein / G-zein to CS mass ratio of 4:1; zein@BA-CS and G-zein@BA-CS nanoparticles obtained in examples 1 and 2 with a BA concentration of 80 μg / mL and a zein / G-zein to CS mass ratio of 4:1.
[0076] The crystal structure and microstructure of the samples were tested, and the in vitro sustained release and water dispersibility tests of BA were conducted.
[0077] 1. Crystal structure characterization of nanoparticles
[0078] The crystal morphology of the sample was analyzed using an X-ray diffractometer. The sample was first freeze-dried into powder and placed in the X-ray diffractometer detector for scanning. The scanning range was 10°-60°, the speed was 5° / min, and the current was 40mA. Zein and BA of the same mass were used as control samples. Ten sets of data were collected for each sample, and three parallels were set for each sample.
[0079] The crystalline state of BA in the composite nanoparticles was studied by X-ray diffraction. Figure 3 As shown, Figure 3 is the XRD spectrum of the sample, Figure 3 It shows that the main characteristic peaks of unencapsulated BA appear at 13.61°, 14.28°, and 19.11°, indicating that BA has a crystalline structure and a high degree of crystallinity. The X-ray diffraction pattern of zein has two broad slow peaks at the diffraction angle 2θ of 11.2° and 13.5°, indicating that zein is an amorphous structure. After BA was encapsulated in particles, the XRD diffraction patterns of zein@BA-CS and G-zein@BA-CS nanoparticles did not show the characteristic crystalline peaks of BA, proving that BA was encapsulated in the particles in an amorphous form. This phenomenon is attributed to the interaction between BA and zein in the particle matrix. After being encapsulated in a nanoscale polymer matrix, BA changes from its original crystalline structure to an amorphous structure. Compared with zein or G-zein nanoparticles, no diffraction peak of protein was observed at 14.5° in the composite nanoparticles of zein or G-zein and CS, indicating that zein or G-zein and CS interact with each other.
[0080] 2. Microstructure of Nanoparticles
[0081] Transmission electron microscope was used to observe the microscopic images of zein-CS, G-zein-CS, zein@BA-CS and G-zein@BA-CS nanoparticles. The suspension of zein-CS, G-zein-CS, zein@BA-CS and G-zein@BA-CS nanoparticles was added dropwise onto the copper mesh containing the carbon support film using a pipette, and then observed on the microscope after drying overnight at a voltage of 100 kV.
[0082] The morphology of zein-CS and zein@BA-CS nanoparticles was observed by transmission electron microscopy. Figure 4 As shown, Figure 4 TEM images of nanoparticles, where A is the microscopic image of zein-CS, B is the microscopic image of G-zein-CS, C is the microscopic image of zein@BA-CS, and D is the microscopic image of G-zein@BA-CS. Figure 4It can be seen that zein-CS, G-zein-CS, zein@BA-CS and G-zein@BA-CS nanoparticles are monodispersed uniform spherical particles, and the introduction of BA does not cause significant changes in the morphology of the nanoparticles.
[0083] 3. In vitro sustained release and water dispersibility test of BA
[0084] Preparation of zein@BA-CS nanoparticle suspension: add 0.5g of zein powder to 100mL of 70% (v / v) ethanol solution, stir magnetically until the protein is completely dissolved to obtain zein solution, add BA powder to the zein solution to make the final concentration of BA 4mg / mL, stir and sonicate at room temperature until BA is completely dissolved to obtain zein nanoparticles (zein / BA) solution loaded with BA. Take 1mL of zein / BA solution and add dropwise to 49mL of CS solution of different concentrations with a syringe and stir for 60min, so that the mass ratio of zein to CS is 4:1, and obtain a composite nanoparticle suspension loaded with BA, that is, a zein-chondroitin sulfate composite nanoparticle (zein@BA-CS nanoparticle) suspension loaded with BA.
[0085] Preparation of G-zein@BA-CS nanoparticle suspension: add 0.5g of G-zein powder to 100mL of 70% (v / v) ethanol solution, stir magnetically until the protein is completely dissolved to obtain G-zein solution, add BA powder to the G-zein solution to make the final concentration of BA 4mg / mL, stir and sonicate at room temperature until BA is completely dissolved to obtain BA-loaded G-zein nanoparticle (G-zein / BA) solution. Take 1mL of G-zein / BA solution and add dropwise to 49mL of CS solution of different concentrations with a syringe and stir for 60min, so that the mass ratio of G-zein to CS is 4:1, and obtain a BA-loaded composite nanoparticle suspension, that is, a BA-loaded G-zein-chondroitin sulfate composite nanoparticle (G-zein@BA-CS nanoparticle) suspension.
[0086] Preparation of free BA ethanol solution: BA powder was added to 100 mL of 70% (v / v) ethanol solution to make the final concentration of BA 8 mg / mL, and the mixture was stirred at room temperature and sonicated until BA was completely dissolved to obtain free BA ethanol solution.
[0087] In vitro sustained release test of nanoparticles:
[0088] 5 mL of each of the freshly prepared zein@BA-CS suspension, G-zein@BA-CS suspension, zein@BA, G-zein@BA nanoparticle suspension, and free BA ethanol solution were added to a dialysis bag with a molecular weight cutoff of 14 kDa and immersed in 25 mL of pH 7.4 phosphate buffer solution containing 0.2% Tween-80. Then it was shaken on a constant temperature shaker at 100 rpm and 37°C. 1 mL of the buffer solution outside the dialysis bag was taken out at 0 h, 1 h, 4 h, 6 h, 12 h, 24 h, 30 h, 36 h, 48 h, 54 h, 60 h and 72 h of shaking, and supplemented with the same volume of blank buffer. The cumulative release of BA was detected by high performance liquid chromatography. The chromatographic column was a Waters Symmetry C18 column (5 μm, 250 mm×4.6 mm), the mobile phase consisted of acetonitrile: water (75:25%, v / v), the flow rate was 1.0 mL / min, the detection wavelength was 210 nm, and the column temperature was maintained at 30°C.
[0089] Water dispersibility test:
[0090] The zein@BA-CS suspension, G-zein@BA-CS suspension, zein@BA suspension, G-zein@BA suspension and free BA ethanol solution were centrifuged at 5000rpm for 10min, the supernatant was filtered through a 0.22μm filter to remove insoluble BA, 1mL of the filtrate was vortexed with 4mL of ethanol for 2min, 15mL of methanol was added to the suspension to extract BA, and the content of BA in the extract was determined by HPLC. HPLC detection conditions: the chromatographic column was a Waters Symmetry C18 column (5μm, 250mm×4.6mm), the mobile phase was composed of acetonitrile: water (75:25%, v / v), the flow rate was 1.0mL / min, the detection wavelength was 210nm, and the column temperature was maintained at 30℃. The effect of the composite nanoparticles on the water dispersibility of BA was analyzed based on the content of BA in the extract.
[0091] The in vitro sustained-release properties of BA-loaded nanoparticles were studied using free BA ethanol solution as a control. Figure 5 The in vitro release graph and water dispersibility graph of the particles, wherein A is the in vitro release graph of the particles in PBS with a pH of 7.4, and B is the water dispersibility graph of the particles (p < 0.05).
[0092] Depend on Figure 5As shown in Figure A, free BA is rapidly released in the buffer, and the BA release is close to 90% after 4 hours. For zein@BA and G-zein@BA, only about 30% of BA is released after 4 hours, and the minimum BA release of zein@BA-CS and G-zein@BA-CS is only 13% after 4 hours. After 72 hours of release, about 90% of BA is released in zein@BA and G-zein@BA, while about 70% of BA is released in zein@BA-CS and G-zein@BA-CS. It can be seen that zein-CS and G-zein-CS composite nanoparticles loaded with BA have a more obvious sustained release effect than zein and G-zein nanoparticles loaded with BA. This is because there is a balanced system of hydrophobic interaction between BA and protein, and BA cannot escape from the system without external interference, thereby prolonging the drug release time. Compared with zein@BA-CS, the sustained release time of G-zein@BA-CS is slightly prolonged, indicating that the hydrophobic interaction between G-zein and BA is stronger. Since the interaction between G-zein and BA and CS is closer than that between zein, the sustained release effect of BA nanoparticles prepared by G-zein is slightly higher than that of BA nanoparticles prepared by zein. In addition, the addition of CS makes a film attached to the surface of BA nanoparticles, further hindering the release of BA from the inside of the particles.
[0093] Figure 5 Figure B shows that free BA is difficult to dissolve in water, with a solubility of only 16.17 μg / mL. However, after interacting with proteins and protein / polysaccharides, the solubility of BA in water is significantly increased. Compared with free BA, the solubility of zein@BA and G-zein@BA in water is increased by 2.27 times and 2.91 times, respectively, while that of zein@BA-CS and G-zein@BA-CS is increased by 3.97 times and 4.24 times, respectively. BA in nanoparticles is easier to disperse in water than free BA. This is because after BA forms nanoparticles with proteins, it encapsulates BA crystals, resulting in less migration of BA molecules and stronger dispersibility in water. The introduction of CS enables the composite nanoparticles to form a membrane-like structure, which better encapsulates BA crystals in the membrane.
[0094] Example 5
[0095] Detection of the antitumor activity of zein-CS nanoparticles and zein@BA-CS nanoparticles
[0096] 1. Cytotoxicity test
[0097] Samples: In basic examples 2-3, zein-CS nanoparticles obtained with a zein to CS mass ratio of 4:1, and G-zein-CS nanoparticles obtained with a G-zein to CS mass ratio of 4:1; in example 1-2, zein@BA-CS nanoparticles obtained with a BA concentration of 80 μg / mL and a zein to CS mass ratio of 4:1, and G-zein@BA-CS nanoparticles obtained with a BA concentration of 80 μg / mL and a G-zein to CS mass ratio of 4:1.
[0098] The CCK-8 kit was used to detect the inhibitory effect of nanoparticles on the proliferation of HepG2 cells.
[0099] HepG2 cell culture and treatment method: When resuscitating HepG2 cells, take the cells out of liquid nitrogen, place them in a 37°C water bath and shake them repeatedly to thaw them as soon as possible, then add fresh culture medium to mix, centrifuge to remove the freezing solution and culture medium, add fresh growth medium again, and re-inoculate them in a culture dish, culture at 37°C, 5% CO2 and saturated humidity, and change the medium every 24 hours. The HepG2 cell growth medium consists of 90% DMEM high-glucose medium, 10% fetal bovine blood, and 100U / mL penicillin / streptomycin.
[0100] Dosing group settings: Blank nanoparticles (zein-CS and G-zein-CS), zein@BA-CS, and G-zein@BA-CS nanoparticles were dissolved in cell growth medium, and the treatment concentrations of each nanoparticle were 0, 10, 20, 40, 80, 160, and 320 μg / mL, respectively. The cells were treated for 24h or 48h, and 6 parallel experiments were set for each treatment.
[0101] CCK-8 kit usage steps:
[0102] HepG2 cells were inoculated in a 96-well plate at a density of 1×104 cells / well. After culturing in the incubator for 24 hours, the original culture medium was aspirated and 100 μL PBS was added to each well to remove the residual culture medium. Then 100 μL of culture medium containing different concentrations of free BA, blank nanoparticles or drug-loaded nanoparticles was added to the wells and cultured for 24 hours or 48 hours, with at least 6 parallel tests in each group. The inhibitory effect of BA and its nanoparticles on the proliferation of HepG2 cells was analyzed using the CCK-8 kit. 10 μL of CCK-8 solution was added to each well, cultured for 2 hours, and the absorbance was measured at 450 nm using an enzyme reader. The cell viability calculation formula is as shown in 3-4:
[0103] Cell survival rate*(%)=[AS-A0] / [AC-A0]×100
[0104] AS: absorbance of wells with cells, CCK-8 solution, and BA nanoparticles;
[0105] A0: absorbance of wells with culture medium and CCK-8 solution but no cells;
[0106] AC: absorbance of wells with cells, CCK-8 solution but without BA nanoparticles;.
[0107] The results of the anti-tumor activity test of nanoparticles using the CCK-8 method are as follows Figure 6 As shown, Figure 6 These are cell activity diagrams of HepG2 cells after 24h and 48h of action of nanoparticles, where A is the 24h action diagram and B is the 48h action diagram.
[0108] Figure 6 The results showed that in HepG2 cells, both empty nanoparticles zein-CS and G-zein-CS showed little cytotoxicity to HepG2 cells, and the cell survival rate was greater than 90%, indicating that the selected zein and CS carrier materials were safe and reliable. The inhibitory effect of zein-CS and G-zein-CS composite nanoparticles loaded with BA on the proliferation of HepG2 cells increased with the increase of the dosage concentration and the extension of the treatment time. It can be seen that the anti-proliferation activity of BA on HepG2 cells is time- and concentration-dependent. The half inhibitory concentration (IC50) of zein@BA-CS and G-zein@BA-CS nanoparticles on HepG2 cells after 24 hours of treatment was 1.377 W·m-1·K-1. 50 ) were 38.34±2.19μg / mL and 33.46±2.06μg / mL, respectively. It can be seen that G-zein@BA-CS nanoparticles have a stronger inhibitory effect on the proliferation of HepG2 cells, and compared with G-zein nanoparticles loaded with BA, IC 50 The value of BA was 35.17±1.01μg / mL. The introduction of CS slightly enhanced its inhibitory effect on HepG2 cell proliferation. After adding CS, the composite nanoparticles could load more BA and improve their anti-tumor activity.
[0109] 2. Cell phagocytosis
[0110] After being embedded in nanoparticles, the way and pathway of small molecule active substances entering cells may change, thus changing their bioavailability. According to the principle of enhanced permeability and retention effect (EPR), small molecule active substances are combined with biomacromolecules such as proteins and polysaccharides to form nanoparticles, which can make small molecule active substances more easily reach and stay in tumor cells. HepG2 cells were used as the research object, and CLSM was used to qualitatively observe the phagocytosis of zein@BA-CS nanoparticles by cells, and the quantitative results were given by flow cytometry. Coumarin-6 has similar solubility to BA and has fluorescent properties, so coumarin-6 was introduced into zein@BA-CS nanoparticles for labeling.
[0111] Sample: G-zein@BA-CS nanoparticles obtained in Example 1 with a BA concentration of 80 μg / mL and a G-zein to CS mass ratio of 4:1; zein@BA-CS nanoparticles obtained in Example 1 with a BA concentration of 80 μg / mL and a zein to CS mass ratio of 4:1.
[0112] Qualitative study: The phagocytosis of BA-loaded nanoparticles by HepG2 cells can be observed by confocal laser scanning microscope (CLSM). The inoculation density on the confocal laser culture dish was 1×10 5 After culturing for 24 hours, the culture medium was discarded and rinsed with PBS once, and 2 mL of coumarin-6-labeled zein@BA-CS and G-zein@BA-CS nanoparticle culture medium (BA concentration was 30 μg / mL) was added, and the culture was continued for 0.5 hours, 2 hours, 4 hours, 6 hours and 12 hours respectively. After discarding the culture medium and rinsing with cold PBS for 3 times, the cell lysosomes were labeled with the culture medium containing the lysosomal red fluorescent probe (LysoTracker Red) for 1 hour, the culture medium was discarded again and rinsed with cold PBS for 3 times, and the cell nuclei were labeled with the culture medium containing DAPI fluorescent dye for 0.5 hours, the culture medium was discarded again and rinsed with cold PBS for 3 times, and then the anti-fluorescence quencher was added and placed under CLSM microscope for observation.
[0113] Quantitative study: The phagocytosis of zein@BA-CS and G-zein@BA-CS nanoparticles by HepG2 cells was detected by flow cytometry. 6HepG2 cells were seeded in 6-well plates at a density of 100 cells / well. After culturing for 24 hours, the culture medium was discarded and culture medium containing 2.5 mL of coumarin-6 labeled zein@BA-CS and G-zein@BA-CS nanoparticles (BA concentration of 80 μg / mL) was added. The culture medium was discarded and rinsed with cold PBS three times, then digested with 0.5 mL of trypsin for 2 minutes, the digestion solution was immediately removed, the cells were resuspended with PBS and centrifuged to collect the cells, and then the fluorescence intensity of the labeled cells was detected by flow cytometry.
[0114] Qualitative research and qualitative research results such as Figure 7 and Figure 8 As shown, Figure 7 The results of HepG2 cell phagocytosis of coumarin-6 labeled G-zein@BA-CS nanoparticles, where A is the CLSM image, B is the flow cytometry research result, and C is the quantitative result of cell phagocytosis (p < 0.05); in A, LysoTracker Red emits red fluorescence to represent lysosomes, DAPI emits blue fluorescence to represent cell nuclei, Coumarin-6NP represents coumarin-6, and overlay represents the superposition effect of the two fluorescent signals. Figure 8 The results of HepG2 cells phagocytizing coumarin-6 labeled zein@BA-CS nanoparticles, where A is the CLSM image, B is the flow cytometry research result, and C is the quantitative result of cell phagocytosis (p < 0.05); in A, LysoTrackerRed emits red fluorescence to represent lysosomes, DAPI emits blue fluorescence to represent cell nuclei, Coumarin-6NP represents coumarin-6, and overlay represents the superposition effect of the two fluorescent signals.
[0115] The uptake of coumarin-6 labeled G-zein@BA-CS nanoparticles by HepG2 cells at different culture times (0 h, 0.5 h, 2 h, 4 h, 6 h and 12 h) is shown in Figure 2. Figure 7As shown in A, at 0.5h, there is almost no green fluorescence, indicating that at this time, G-zein@BA-CS nanoparticles have hardly entered the cells. Obvious green fluorescence can be seen at 2h, at which time a small amount of G-zein@BA-CS nanoparticles have accumulated in the cells. Then at 4h and 6h, the green fluorescence signal becomes increasingly stronger, and slightly weakened at 12h, indicating that the phagocytosis of G-zein@BA-CS nanoparticles by HepG2 cells reaches its peak within 6-12h. In addition, the green fluorescence signal only appears in the cytoplasm, not in the nucleus, indicating that G-zein@BA-CS nanoparticles enter the cell by endocytosis. After incubation for 6h, the green fluorescence intensity further increased, and it can be observed that the G-zein@BA-CS nanoparticles have a strong co-localization effect with the red fluorescence of the lysosomes, indicating that after entering the cells, the G-zein@BA-CS nanoparticles are mainly accumulated in the lysosomes of the cytoplasm. Figure 7 As shown in B and C, the fluorescence intensity in the cells increased significantly with the extension of incubation time. For HepG2 cells, the percentage of cells engulfing nanoparticles decreased after 12 hours of engulfment, indicating that the cell uptake of G-zein@BA-CS nanoparticles has reached its peak.
[0116] The phagocytosis of zein@BA-CS nanoparticles by cells is shown in Figure 2. Figure 8 As shown by Figure 8 As shown in Figure A, the phagocytosis process of zein@BA-CS by HepG2 cells is basically the same as that of G-zein@BA-CS. Both nanoparticles enter the cells through endocytosis and are mainly distributed in the cytoplasm without entering the nucleus. Figure 8 As shown in Figures B and C, the fluorescence intensity in the cells increased significantly with the extension of the incubation time. After 4 hours of phagocytosis by HepG2 cells, the percentage of cells that phagocytized zein@BA-CS nanoparticles did not change significantly, and the time to reach the peak was shorter than that of G-zein@BA-CS nanoparticles. The nanoparticles prepared by G-zein had a more obvious sustained release effect in the cells.
[0117] 3. Cell Immunofluorescence
[0118] Samples: free BA (30 μg / mL, prepared according to the method of Example 4); zein@BA-CS prepared according to the method of Example 1, wherein the BA concentration is 30 μg / mL and the mass ratio of zein to CS is 4:1; G-zein@BA-CS nanoparticles prepared according to the method of Example 2, wherein the BA concentration is 30 μg / mL and the mass ratio of G-zein to CS is 4:1.
[0119] 1×10 5HepG2 cells were inoculated at a density of 100 cells / well in a 24-well culture dish. After culturing for 24 hours, the culture medium was aspirated and discarded. 1 mL of culture medium containing free BA, zein@BA-CS, and G-zein@BA-CS nanoparticles was added to each well and culture was continued for 24 hours. At least 6 parallel experiments were performed in each group. After the culture time was reached, the culture medium was aspirated and discarded, and the cells were rinsed with cold PBS three times. The cells were fixed with 4% paraformaldehyde solution for 30 minutes, and then permeabilized with 0.1% Triton X-100 (1 mL) for 2 minutes. The permeabilization solution was aspirated and discarded. After rinsing with PBS three times, 10% bovine serum albumin was added for blocking for 30 minutes. Then, the primary antibody was added for overnight incubation at 4°C, followed by incubation with FITC-labeled secondary antibody at 37°C for 60 minutes. The cells were rinsed with PBS three times and the cell nuclei were labeled with DAPI for 30 minutes, and then observed under an inverted fluorescence microscope. The results are shown in Fig. 9 As shown, Fig. 9 These are the microtubule immunofluorescence images of HepG2 cells treated with free BA, zein@BA-CS and G-zein@BA-CS for 24 hours. DAPI emits blue fluorescence to represent the cell nucleus, FITC emits green fluorescence to represent the protein, Overlay represents the superposition effect of the two fluorescent signals, DAPI, FITC and Overlay are fluorescence microscope images, and CLSM is a confocal microscope image.
[0120] BA mainly causes cytoskeleton collapse by upregulating the expression level of intracellular tubulin, thereby causing cell apoptosis. Immunofluorescence technology is often used to observe the changes in cytoskeleton proteins. Fig. 9 The results showed that the cell microtubule structure of untreated HepG2 cells was intact, but after treatment with free BA and zein@BA-CS nanoparticles, the cells showed excessive microtubule proliferation, and some cells were deformed in morphology, the cytoskeleton was rearranged, and even collapsed, leading to cell apoptosis.
[0121] 4. Cell apoptosis detection test
[0122] Samples: zein-CS nanoparticles obtained in Example 1 with a mass ratio of zein to CS of 4:1; G-zein-CS nanoparticles obtained in Example 1 with a mass ratio of G-zein to CS of 4:1; zein@BA-CS nanoparticles obtained in Example 1 with a BA concentration of 20 μg / mL and a mass ratio of zein to CS of 4:1; G-zein@BA-CS nanoparticles obtained in Example 2 with a BA concentration of 20 μg / mL and a mass ratio of G-zein to CS of 4:1.
[0123] HepG2 cell suspension was inoculated in a 6-well plate at a density of 1×10 6 / well. Place the 6-well plate in an incubator and culture for 24 hours. After the cells adhere to the wall, remove the culture medium and add culture medium containing blank nanoparticles (zein-CS, G-zein-CS), zein-CS@BA, G-zein-CS@BA nanoparticles and free BA suspension (BA concentration is 20μg / mL) respectively. Set up a blank control. After continuing to culture for 24 hours, aspirate the culture medium, digest with 0.5mL of trypsin, and collect the cells by centrifugation at 1000rpm. Add AnnexinV-FITC conjugate (195μL) and Annexin V-FITC (5μL) into a centrifuge tube, then add 10μLPI and shake well. After reacting at room temperature in the dark for 15 minutes, enter the flow cytometer for detection. Analyze the results using FlowJo software. The results are as follows Fig.10 As shown, Fig.10 Figure 2 is the effect of nanoparticles on cell apoptosis, wherein A is the effect of nanoparticles on cell apoptosis after HepG2 cells were treated with nanoparticles detected by flow cytometry (cell scatter plot), and B is the percentage of cell apoptosis caused by nanoparticles (the sum of the percentages of early and late cell apoptosis) (p < 0.05).
[0124] Fig.10 The results showed that there was no significant difference in apoptosis of HepG2 cells after treatment with blank nanoparticles compared with the blank control group. The apoptosis rate of the blank control group was 5.32%, and the percentages of early and late apoptotic cells caused by zein@BA-CS and G-zein@BA-CS nanoparticles treatment increased to 19.45% and 22.26%, respectively (P<0.05), indicating that compared with zein@BA-CS composite nanoparticles, G-zein@BA-CS composite nanoparticles have stronger cytotoxicity to HepG2 cells, which is consistent with the previous CCK-8 experimental results. Zein@BA-CS and G-zein@BA-CS nanoparticles enter cells through endocytosis. After a certain period of time, the accumulated BA in the cells exerts an anti-tumor effect and causes apoptosis of HepG2 cells. There is an adhesive interstitial fluid around the cells. The zein@BA-CS nanoparticles can avoid the influence of the mucus layer through endocytosis, allowing BA to enter the cells smoothly.
[0125] 5. Extraction of total cell RNA and real-time fluorescence quantitative PCR
[0126] Caspase-3 pathway is closely related to cell apoptosis. Caspase-3 and Bax promote tumor cell apoptosis, while Bcl-2 inhibits the process of cell apoptosis. To study the effect of BA composite nanoparticles on Caspase-3, a pathway related to cell apoptosis, the expression of Caspase-3, Bax and Bcl-2 gene mRNA was detected by real-time fluorescence quantitative PCR.
[0127] Samples: zein-CS nanoparticles obtained in Example 1 with a mass ratio of zein to CS of 4:1; G-zein-CS nanoparticles obtained in Example 1 with a mass ratio of G-zein to CS of 4:1; zein@BA-CS nanoparticles obtained in Example 1 with a BA concentration of 30 μg / mL and a mass ratio of zein to CS of 4:1; G-zein@BA-CS nanoparticles obtained in Example 2 with a BA concentration of 30 μg / mL and a mass ratio of G-zein to CS of 4:1.
[0128] HepG2 cells were cultured at a density of 1.0 × 10 5 The cells were inoculated in 12-well plates at a density of 80%. When the cell density reached 80%, zein-CS, G-zein-CS, zein@BA-CS, and G-zein@BA-CS (BA concentration was 30 μg / mL) were added respectively and the cells were cultured for 48 h. After the incubation, the cells were washed with PBS and the total RNA in the cells was extracted using Trizol reagent.
[0129] The collected cells were lysed into a uniform solution, and then 200 μL of chloroform was added to mix, and the solution was allowed to stand at room temperature for 2 min, and then centrifuged at 12000 rpm for 10 min. The supernatant was mixed with an equal volume of isopropanol, incubated on ice for 15 min, and centrifuged at 12000 rpm for 15 min. The supernatant was discarded, and 1 mL of 75% ethanol was added to wash the precipitate, and the solution was centrifuged at 4°C and 7500 rpm for 5 min. The supernatant was discarded, and the solution was dried at room temperature for 10 min. Finally, 40 μL of DEPC water was added to dissolve the RNA, and the solution was placed in a -80°C refrigerator for use. The RNA concentration was determined using NanoDrop2000, and RNA samples with OD 260 / 280 values between 1.9 and 2.1 were used for subsequent experiments.
[0130] The synthesis of the first strand of cDNA was performed according to the instructions of the RT Reagent Kit with gDNA Eraser reverse transcription kit, and the real-time fluorescence quantitative PCR was performed according to the instructions of the TB Green II kit, with β-actin (actin beta, β-actin) as the internal reference gene. The primer sequences refer to Table 3, and the reaction procedures are as follows: (1) pre-denaturation at 95°C for 30s; (2) 95°C, 5s to 60°C, 30s, set 40 cycles; (3) add melting curve.
[0131] Table 3 Real-time fluorescence quantitative PCR primer sequences
[0132]
[0133] The results are as follows Fig.11 As shown, Fig.11This is the effect of nanoparticles on genes in the Caspase-3 signaling pathway of cell apoptosis (p < 0.05).
[0134] Fig.11 The results showed that compared with the zein-CS and G-zein-CS groups, the Caspase-3 and Bax gene expressions of the BA-loaded nanoparticle groups zein@BA-CS and G-zein@BA-CS were significantly increased (P<0.05), the Bcl-2 gene expression was significantly decreased (P<0.05), and the Bax / Bcl-2 expression was also significantly increased (P<0.05). Compared with the zein@BA-CS group, the Caspase-3 and Bax gene expressions of the G-zein@BA-CS group were significantly increased, and the Bcl-2 gene expression was significantly decreased. G-zein@BA-CS can induce apoptosis of tumor cells.
[0135] 6. Extraction of total cell protein and Western blot
[0136] Samples: zein-CS nanoparticles obtained in Example 1 with a mass ratio of zein to CS of 4:1; G-zein-CS nanoparticles obtained in Example 1 with a mass ratio of G-zein to CS of 4:1; zein@BA-CS nanoparticles obtained in Example 1 with a BA concentration of 30 μg / mL and a mass ratio of zein to CS of 4:1; G-zein@BA-CS nanoparticles obtained in Example 2 with a BA concentration of 30 μg / mL and a mass ratio of G-zein to CS of 4:1.
[0137] HepG2 cells were cultured at a density of 1.0 × 10 5 / mL was inoculated in a 12-well plate. When the cell density reached 80%, zein-CS, G-zein-CS and zein@BA-CS, G-zein@BA-CS (BA concentration was 30μg / mL) were added respectively and the cells were cultured for 48h. After incubation, the cells were washed with PBS and the intracellular protein was extracted: (1) The culture medium was aspirated, the cells were rinsed with pre-cooled PBS buffer for 3 times, and 200μL RIPA lysis buffer (containing protease inhibitors) was added. (2) Gently shake to mix, scrape the cells with a cell scraper, collect them in a 1.5mL centrifuge tube, vortex for 30 seconds, lyse on ice for 30min, centrifuge at 4℃, 13000rpm for 10min, collect the supernatant, which is the total cell protein. (3) The concentration of each protein sample was determined using a BCA kit. (4) 5× protein loading buffer was added to ensure that the final protein concentration of each sample was consistent, boiled in boiling water for 10min to fully denature the protein, and stored at -80℃ for later use.
[0138] Western blot protein expression detection: (1) Absorb 20 μg of total protein for SDS-PAGE electrophoresis. (2) Use a semi-dry transfer device to transfer the target protein band to a PVDF membrane soaked in methanol. After blocking with 5% skim milk powder for 2 hours, incubate the primary antibody overnight at 4°C on a shaker. (3) After washing the membrane 3 times with TBST (15 minutes each time), incubate the secondary antibody for 1 hour on a shaker at room temperature. (4) After washing the membrane 3 times with TBST (10 minutes each time), prepare ECL luminescent solution and use a chemiluminescent imager to detect the target protein band. β-actin was used as an internal reference for relative protein abundance.
[0139] Western blot was used to detect the expression of Bcl-2, Bax and Caspase-3 proteins in HepG2 cells to further explore the effect of BA composite nanoparticles on the Caspase-3 pathway. Fig.12 As shown, Fig.12 The figure is the effect of nanoparticles on the protein of Caspase-3 signaling pathway of cell apoptosis, wherein A is the expression of apoptosis-related protein, and B is the statistical analysis result of the expression of apoptosis-related protein (p<0.05).
[0140] Depend on Fig.12 It can be seen that compared with the zein-CS and G-zein-CS groups, the expression of Bax and Caspase-3 proteins in the zein@BA-CS and G-zein@BA-CS groups increased significantly, the expression of Bcl-2 protein decreased significantly, and the expression of Bax / Bcl-2 protein also increased significantly (P<0.05), indicating that both zein@BA-CS and G-zein@BA-CS nanoparticles can activate the Caspase-3 signaling pathway and induce tumor cell apoptosis. In addition, compared with the zein@BA-CS group, the levels of Caspase-3 and Bax proteins in the G-zein@BA-CS group increased significantly, and the level of Bcl-2 protein decreased significantly, indicating that the effect of G-zein@BA-CS composite nanoparticles in inducing tumor cell apoptosis is better than that of zein@BA-CS nanoparticles.
[0141] There are three main pathways of cell apoptosis: the extrinsic pathway triggered by death receptors on the cell surface; the intrinsic pathway activated by stress conditions such as chemotherapy drugs; and the endoplasmic reticulum stress-induced cell apoptosis pathway. Currently, most studies on apoptosis pathways are focused on detecting the expression levels of several classic apoptosis-related genes and proteins, including Bax, Bcl-2, and Caspase-3. Many apoptosis signal transductions are ultimately caused by Caspase, and Caspase-3 is the final execution gene of apoptosis. Studies have shown that BA can increase intracellular Ca 2+concentration, leading to mitochondrial membrane potential depolarization and increasing the activity of Caspase-3, Caspase-8 and Caspase-9 to induce apoptosis of cervical cancer cells.
[0142] The above results showed that zein@BA-CS nanoparticles changed the expression levels of apoptosis-related genes and proteins in HepG2 cells, further indicating that zein@BA-CS nanoparticles can induce apoptosis of liver cancer cells.
[0143] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing glycosylated zein-chondroitin sulfate composite nanoparticles loaded with betulinic acid, characterized in that: The product is prepared from betulinic acid, glycosylated zein and chondroitin sulfate by using an anti-solvent method.
2. The preparation method according to claim 1, characterized in that: The glycosylated zein is obtained by subjecting zein to a glycosylation reaction using glucose.
3. The preparation method according to claim 2, characterized in that: The glycosylation reaction specifically comprises the following steps: The zein solution is dissolved in a KCl-NaOH buffer solution with a concentration of 0.1-0.3 mol / L and a pH value of 12.0-14.0 to obtain a zein solution, glucose is added to the zein solution to cause a Maillard reaction, the reaction is carried out at 80-90° C. for 1-4 hours, the supernatant is separated by centrifugation, and the pH value of the supernatant is adjusted to 7.0 with hydrochloric acid; the obtained supernatant solution is dialyzed and then dried to obtain glycosylated zein.
4. The preparation method according to claim 3, characterized in that: The grafting degree of glycosylated zein is 20-25%.
5. The preparation method according to claim 1, characterized in that: The mass ratio of betulinic acid, glycosylated zein and chondroitin sulfate is 1-9:1-5:1-5.
6. The preparation method according to claim 5, characterized in that: The mass ratio of betulinic acid, glycosylated zein and chondroitin sulfate is 2-5:4-5:1-5.
7. The preparation method according to claim 6, characterized in that: The mass ratio of betulinic acid, glycosylated zein and chondroitin sulfate is 2-5:4:
1.
8. The preparation method according to any one of claims 1 to 7, characterized in that: The anti-solvent method is specifically: Step 1): dissolving betulinic acid in an ethanol aqueous solution of glycosylated zein, wherein the volume fraction of the ethanol aqueous solution is 65-74%, to obtain a solution 1; Step 2): The aqueous solution of chondroitin sulfate is mixed with the solution 1 to react, so as to obtain glycosylated zein-chondroitin sulfate composite nanoparticles loaded with betulinic acid.
9. The preparation method according to claim 8, characterized in that: The volume fraction of the ethanol aqueous solution in step 1) is 70%.
10. A glycosylated zein-chondroitin sulfate composite nanoparticle loaded with betulinic acid, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 9.
11. The glycosylated zein-chondroitin sulfate composite nanoparticles loaded with betulinic acid according to claim 10, characterized in that: The particle size of the betulinic acid-loaded glycosylated zein-chondroitin sulfate composite nanoparticles is 160-180 nm.
12. Use of the betulic acid-loaded glycosylated zein-chondroitin sulfate composite nanoparticles prepared by the preparation method according to any one of claims 1 to 9 or the betulic acid-loaded glycosylated zein-chondroitin sulfate composite nanoparticles according to any one of claims 10 to 11 in the preparation of anti-tumor drugs.
13. The use according to claim 12, characterized in that: The tumor includes liver cancer.
